Isolation of a temperate bacteriophage encoding the type III effector protein SopE from an epidemic Salmonella typhimurium strain - Mirold, Susanne (The National Academy of Sciences, 1999)
Salmonella typhimurium employs the specialized type III secretion system encoded in pathogenicity island 1 (SPI1) to translocate effector proteins into host cells and to modulate host cell signal transduction. The SPI1 type III system and the effector proteins are conserved among all salmonellae and are thought to be acquired by horizontal gene transfer. The genetic mechanisms mediating this horizontal transfer are unknown. Here, we describe that SopE, a SPI1-dependent translocated effector protein, is present in relatively few S. typhimurium isolates. We have isolated a temperate phage that encodes SopE. Phage morphology and DNA hybridization, as well as partial sequence information, suggest that this phage (SopEΦ) is a new member of the P2 family of bacteriophages. By lysogenic conversion this phage can horizontally transfer genes between different S. typhimurium strains. Strikingly, most of the isolates harboring SopEΦ belong to the small group of epidemic strains of S. typhimurium that have been responsible for a large percentage of human and animal salmonellosis and have persisted for a long period of time. Our data suggest that horizontal transfer of type III dependent effector proteins by lysogenic infection with bacteriophages (lysogenic conversion) may provide an efficient mechanism for fine-tuning the interaction of Salmonella spp. with their hosts.